Boys’ Experience of Physical Education When Their Gender Is in a Strong Minority - Lagestad, Pål; Ropo, Eero; Bratbakk, Tonje (Frontiers in Psychology, 2021)
A literature search indicates an absence of research into boy’s experiences of physical education(PE) in classes in which there is a significant majority of girls. The aim of the study was to examine how boys in such classes experience their PE lessons. The methodological approach was qualitative and data were collected with interviews of 13 boys in classes with more than 90% girls at the Norwegian high school. The data were analysed with QSR NVivo 10 (London), focused on creating categories of meaning, in which students’ experiences were taken as subjectively true (Armour and Griffiths, 2012). The data are based on subjective constructions, which students constructed as part of their own interpretations and reflections on what had occurred in PE at the school. Results of the study came out in the form of three main findings. Two of those relate to a negative experience, and the third to a positive experience of PE. The boys mostly felt that they are physically superior and have to consider the girls. Furthermore, the boys reported little challenge and feelings of mastery whilst being together with passive girls who are allowed to choose the activities. However, the boys found it easier to show off in front of the teachers and classmates when there are just few boys in the class. The results are discussed in relation to gender related theory on how the respondents are producing a traditional male gender in PE, through their mastery, strength and ambition to compete. We suggest a new approach of teaching that is more student-centered. A strategy could be to include other activities than sport-based activities into PE – activities that do not require strength and other athletic skills leading to feelings of hegemonic masculinity. A larger focus on social interactions during PE classes – activities where students' sex is not as important as in traditional teacher-centered and sport-centered PE classes, may be a good strategy.